2008
DOI: 10.1258/td.2007.070344
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of splenic injury in the tropics

Abstract: We undertook this study in order to determine whether the conservative management of splenic injuries is a safe practice in a low-volume tropical hospital. We evaluated 69 consecutive patients with splenic injury prospectively. The outcome measures were morbidity and mortality rates, overall hospital stay and blood transfusion requirements. Spleen preservation was achieved in 85% (59) of cases. Of the 16 patients who underwent splenic surgery, six had splenorraphy (38%). The overall mortality was 4.3% (3) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There are increased risks of infection and sepsis who had a splenectomy, so NOT is indispensable for children particularly. Kuzma et al [8] reported mean systolic blood pressure in a NOT group as 98 mmHg and in a surgically treated group as 84 mmHg. We detected the same parameter at the level of 105 mmHg in group I and 95 mmHg in group II; mean diastolic blood pressures were 70 mmHg in group I and 65 mmHg in group II.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There are increased risks of infection and sepsis who had a splenectomy, so NOT is indispensable for children particularly. Kuzma et al [8] reported mean systolic blood pressure in a NOT group as 98 mmHg and in a surgically treated group as 84 mmHg. We detected the same parameter at the level of 105 mmHg in group I and 95 mmHg in group II; mean diastolic blood pressures were 70 mmHg in group I and 65 mmHg in group II.…”
Section: Discussionmentioning
confidence: 98%
“…Blood transfusions were performed in four patients (12%) in the nonoperative group and in five patients (83%) in the operative group in Thompson et al study. Jerzy et al [8] indicated that patients in the NOT group needed 0.81 unit of blood and the OT group they needed 2.91 units of blood (p<0.001). In this study the rate of blood transfusion in group I was 45% and in group II it was 100%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, many surgical procedures of the spleen have been described in previous literature (application of haemostatic agents, segmental resection, mesh-splenorrhaphy, stapler resection and auto-transplantation) (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%